«МИСТИКА» И «ДУХОВНЫЙ ОПЫТ», ИЛИ В ПРОСТРАНСТВЕ УСКОЛЬЗАЮЩИХ ГРАНИЦ - КОМПАНИЕЦ, ЛИЛИЯ ВИКТОРОВНА (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье проводится анализ смыслового поля термина «мистика», а такжеспецифики его отношения к «духовному опыту». Проводится изучение проблемыдемаркации между обозначенными понятиями. Устанавливается подвижность границ,их взаимное смысловое проникновение, дополнение. Мистика презентуется какуниверсальное комплексное явление культуры, атрибутом и источником котороговыступает «духовный опыт». Даётся авторское определение термина «мистика».Компанієць Л.В. «МІСТИКА» І «ДУХОВНИЙ ДОСВІД», АБО У ПРОСТОРІЗНИКАЮЧИХ МЕЖ У статті проводиться аналіз смислового поля терміна «містика», атакож специфіки його відношення до «духовного досвіду». Проводиться вивченняпроблеми демаркації між зазначеними поняттями. Встановлюється рухливість меж, їхвзаємне проникнення, доповнення. Містика презентується як універсальне комплекснеявище культури, атрибутом і витоком якого виступає «духовний досвід». Даєтьсяавторське визначення терміна «містика».Ключові слова: містика, «духовний досвід», поняття, явище, визначення.Kompaniyets L.V. MYSTICS AND SPIRITUAL EXPERIENCE OR IN THE SPACE OFELUSIVE LIMITS The relevance of mystics is substantiated in the article. It is emphasized thatin the modern world a sustained interest to mysticism from everyday and religiousconsciousness, different spheres of society, is observed. The relevance of the topic is evident inlight of everyday realities of modern mass culture, confirmed with the increasing attention to thephenomena of this kind within scientific communities. As the history of the mankind evolutionproves, mystics has become popular and expanded its geographic distribution in transition andcrisis.The semantic field of the term "mystics" is investigated, as well as the specifics of itsrelation to the "spiritual experience". The comprehension of the problem of demarcationbetween the specified terms is conducted. The flexibility of boundaries is defined, the flow ofmeanings from one concept to another is fixed.Mystics is presented as the foundation on which the whole space of human belief in asupernatural world is built, the dominant form of its incarnation on the plane of matter appearsto be "spiritual experience", which is defined by us as an attribute of mystics, and hence of anyreligious, mystical tradition and culture. Mystical experience reveals itself as its source andground.Proceeding from the kaleidoscope of scattered interpretations of the term "mystics" weoffer the perspective of its consideration. As a result, the author's definition of the term "mystics"is suggested. By mystics we understand the multifaceted cultural phenomenon associated withmystery, ideal worlds, having multiple forms of its incarnation and manifestation on the plane ofmatter, the source and mode of existence of which stands the "mystical experience". Mystics isalso presented as a universal complex cultural phenomenon.Keywords: mystics, spiritual experience, elusive boundaries, a supernatural world.